Immediate extubation in cardiac surgery: evaluation using electroencephalogram Extubação imediata em cirurgia cardíaca: avaliação pelo eletroencefalograma - Valdester Cavalcante Pinto Jr. (Brazilian Journal of Cardiovascular Surgery, 2003)
BACKGROUND AND OBJECTIVES:The current techniques of anesthesia employed in cardiac surgery leading to immediate extubation depend on adequate analgesia and titration of anesthetic drugs. We sought to determine the best possible moment of extubation, using the bispectral index of the electroencephalogram. METHOD: Twelve ASA III patients were analyzed. Seven (58.4%) were children (Group I), submitted to correction of congenital cardiac defects with ages ranging from 0 to 7 years. Five adults (Group II), with ages ranging from 30 to 75 years, underwent coronary artery bypass grafts. In Group I spinal anesthesia (L5-S1) using hyperbaric 0.5% bupivacaine (0.5mg/kg) and morphine (5µg/kg) was chosen. In Group II epidural anesthesia (T3-T4) with catheter placement plus ropivacaine (60mg) and morphine (2mg) were employed. For the induction of anesthesia fentanila (4µg/kg), muscle relaxant and propofol (to bring the bispectral index value down to 30) were utilized. General anesthesia was maintained with sevofluorane, maintaining the bispectral index value between 40 and 60. Extubation was programmed at a bispectral index value of 90. RESULTS: All patients were extubated up to one hour after the end of the surgical procedure, 91.6% of them in the operating room. All had the cognitive functions preserved without history of explicit memory or pain (adults and children who were able to speak), nor facial expression of pain (small children). Four (57%) patients in Group I and one (20%) in Group II had post-operative pruritus. Two patients (28%) in Group II had emesis. CONCLUSIONS: The results suggest that the technique employed is safe and effective, as long as the criteria for its use are strictly observed. INTRODUÇÃO: As técnicas empregadas em cirurgia cardíaca visando a extubação imediata (EI) dependem de analgesia adequada e titulação de drogas anestésicas. OBJETIVO: A finalidade deste estudo é analisar a EI, utilizando eletroencefalograma (índice bispectral - BIS) para adequar o melhor momento de extubação. MÉTODO: Foram analisados 12 pacientes, ASA III, 7 crianças (Grupo I) 58,4%, com idades entre 0 e 7 anos, submetidas a correção cirúrgica de cardiopatias congênitas e 5 adultos (Grupo II), com idades entre 30 e 75 anos, submetidos a revascularização do miocárdio. No Grupo I realizou-se raquianestesia entre L5 e S1 com injeção de marcaína pesada (0,5 mg/kg) e morfina (5µg/kg). No Grupo II realizou-se bloqueio epidural entre T3 e T4, com introdução de cateter e injeção de 60mg de ropivacaína e 2mg de morfina. Na indução da anestesia, empregamos: Fentanil 4 µg/kg, propofol até BIS igual a 30 e relaxante muscular. A anestesia geral foi mantida com sevoflurano para BIS entre 40 e 60. Foi programada extubação quando o BIS atingisse 90. RESULTADOS: Todos os pacientes foram extubados até 1 hora após o término da operação, sendo 91,6% na sala de operações, com função cognitiva preservada, sem história de memória explícita, dor (adultos e crianças maiores) ou expressão facial de dor (crianças menores). Cinqüenta e sete por cento (4) dos pacientes do Grupo I e 20% (1) Grupo II apresentaram prurido e 28% (2) Grupo I apresentaram vômitos. CONCLUSÕES: A técnica empregada mostrou-se segura e eficaz, desde que observados critérios rígidos para sua execução.